Percentage Predicted Peak Oxygen Consumption in People With Fontan Circulation: A Rapid Systematic Scoping Review and Validation Study - Curtis A. Wadey; Owen W. Tomlinson; Alan R. Barker; A. Graham Stuart; Derek L. Tran; Karina Laohachai; Julian Ayer; Robert G. Weintraub; Rachael Cordina; Craig A. Williams (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Peak oxygen consumption (peak V̇O2$$ \dot{V}{O}_2 $$) is routinely measured in people who have congenital heart disease and is reported as a percentage of predicted value, based upon age‐ and sex‐matched normative reference values (NRVs). This study aimed to identify which NRVs are being used, assess whether NRVs are being applied appropriately, and evaluate if recommended NRVs are valid when applied to people with congenital heart disease. Methods and Results A systematic scoping review identified studies that reported peak V̇O2$$ \dot{V}{O}_2 $$ percentage of predicted value in people with congenital heart disease. A modified risk of bias tool evaluated the included studies. Forty‐five studies reported peak V̇O2$$ \dot{V}{O}_2 $$ percentage of predicted value, and only 21 (47%) studies described or provided a reference on how their percentage of predicted value was calculated. The most cited NRVs were from Wasserman (n=12) and Cooper and Weiler‐Ravell (n=7). Risk of bias analysis judged 63% of studies as having some concerns. The NRVs recommended by the American Heart Association were applied to participants with a Fontan circulation (n=70; aged 26.5±6.4 years; 59% women) to examine validity. Predicted peak V̇O2$$ \dot{V}{O}_2 $$ values from the Wasserman NRV was not significantly associated to measured peak V̇O2$$ \dot{V}{O}_2 $$ values (men: b=0.31, R2≤0.01; women: b=0.07, R2=0.02). Conclusions Numerous NRVs have been applied to individuals with congenital heart disease and are often poorly reported and inappropriately matched to participants. The Wasserman NRV was the most cited but showed poor validity when applied to a Fontan cohort.